Losses among selected small-scale fisherfolks due to coastal pressures a case in Barangay Sto. Nino Sur, Villa, Iloilo City, Philippines - Banas, Jonathan Chris C (2023.)
Coastal environments continue to degrade despite efforts taken on a global to local scale to mitigate impacts of coastal pressures which include natural and anthropogenic phenomena. Worldwide trends point towards declining environmental quality, depleting resources that are otherwise renewable, and loss of habitats. As a results, it impedes growth and diminishes the quality of life of coastal communities embedded in their local resources. Small-scale fisherfolks in the community Sto. Niño Sur, Villa, Iloilo City possess a wide range of goods and services from their coastal area and fishing grounds. However, in recent years, there have been observed cases of coastal pressures and losses that have been recurring in the community where small-scale fisherfolks reside. This study described the community's profile, the small-scale fisherfolk's characteristics, their fishing gears, resources, experienced coastal pressures and direct losses. This study estimated the losses through the value of docking areas, foregone fishing income, substitutes for coastal recreation, fishing activities, and culturally-significant trees by using market price method which amounted to a total of Php 2,377,902.00 within the span of 20 years. This study also aimed to provide possible solutions and recommendations to coastal pressures. Even though societal responses were done to address these coastal pressures since 2004, 64.28% of the(n=42) study participants in the community did not feel their effectivity. Since there are a lot of people, particularly small-scale fisherfolks residing in the coastal areas of the study site, coastal pressures and the aforementioned losses are major threats to their daily lives. The study suggests that coastal communities, non-governmental organizations, academe, and government should work together in creating and administering effective societal responses to the existing problems in the coastal areas through education, adaptation strategies, alternative livelihood, and better policy implementation that can address the losses among small-scale fisherfolks due to coastal pressures.
Special Problem (Master of Marine Affairs) -- [Miagao, Iloilo] : University of the Philippines Visayas, July 2023.